Protein Composition and Baking Quality of Wheat Flour as Affected by Split Nitrogen Application - Xue, Cheng; Matros, Andrea; Mock, Hans-Peter; Mühling, Karl-Hermann (Frontiers in Plant Science, 2019)
Baking quality of wheat flour is determined by grain protein concentration (GPC) and its composition and is highly influenced by environmental factors such as nitrogen (N) fertilization management. This study investigated the effect of split N application on grain protein composition and baking quality of two winter wheat cultivars, Tobak and JB Asano, belonging to different baking quality classes. Bread loaf volumes in both cultivars were enhanced by split N application. In contrast, GPC was only significantly increased in JB Asano. Comparative 2-DE revealed that the relative volumes of 21 and 28 unique protein spots were significantly changed by split N application in Tobak and JB Asano, respectively. Specifically, the alterations in relative abundance of certain proteins i.e. globulins, LMW-GS, α- and γ-gliadins as well as α-amylase/trypsin inhibitors were more sensitive to split N application. Furthermore, certain proteins identified as globulins and alpha-amylase inhibitors were changed in both wheat cultivars under split N application. These results implied that the functions of these unique proteins might have played important roles in affecting baking quality of wheat flour, especially for cultivars (i.e. Tobak in the present study) the baking quality of which is less dependent on GPC.